Synopsis of the Peruvian species of Epidendrum (Orchidaceae: Laeliinae) belonging to the Scabrum group, subgroup Soratae: diversity and description of a new species - Quispe-Melgar, Harold Rusbelth; Santiago Ayala, Elizabeth; Llacua-Tineo, Yashira Stefani; Hágsater, Eric (Phytotaxa, 2023)
We present a synopsis of the species of the genus Epidendrum belonging to Soratae subgroup, Scabrum group in Peru. Information on their distribution, elevation ranges, phenology, and conservation status in Peru is provided. For this purpose, we conducted a review of herbarium plant material, the AMO-DATA herbarium database, and the original publications of the species. We recorded 27 species with the greatest species richness in the eastern cordillera from north to south and the highest concentration of endemic species in the central region of the Peruvian Andes. Epidendrum centralense is described and illustrated as a new species and compared with Epidendrum soratae, which is the closest species. The new species differs mainly in the color of the flowers that are green-brown with an irregular red brown tinge, the length and shape of the leaves that are 2.0–2.5 cm long, lanceolate, obtuse, the cuniculus forming a small vesicle in the pedicel, and the size and shape of the lip that is 3.1–4 × 5 mm, transversely reniform and apically obtuse. The new species represents an important record for the flora associated with the high elevation Andean Forest of Polylepis from central Peru. We provide a key to the Peruvian members of Epidendrum belonging to the Soratae subgroup.